-1(3z+4)=6z+-3(3z+2)

Simple and best practice solution for -1(3z+4)=6z+-3(3z+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1(3z+4)=6z+-3(3z+2) equation:


Simplifying
-1(3z + 4) = 6z + -3(3z + 2)

Reorder the terms:
-1(4 + 3z) = 6z + -3(3z + 2)
(4 * -1 + 3z * -1) = 6z + -3(3z + 2)
(-4 + -3z) = 6z + -3(3z + 2)

Reorder the terms:
-4 + -3z = 6z + -3(2 + 3z)
-4 + -3z = 6z + (2 * -3 + 3z * -3)
-4 + -3z = 6z + (-6 + -9z)

Reorder the terms:
-4 + -3z = -6 + 6z + -9z

Combine like terms: 6z + -9z = -3z
-4 + -3z = -6 + -3z

Add '3z' to each side of the equation.
-4 + -3z + 3z = -6 + -3z + 3z

Combine like terms: -3z + 3z = 0
-4 + 0 = -6 + -3z + 3z
-4 = -6 + -3z + 3z

Combine like terms: -3z + 3z = 0
-4 = -6 + 0
-4 = -6

Solving
-4 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 | | 5(-3b+2)=40 | | 34+a+(-48.08)*1.414213562=0 | | 10+9(x-2)=13x-4(x+4) | | 10k+13r=(276)(12) | | 10a+120=8 | | -(2x-8)+1=7x+9(1-x) | | 95-7x=20x+17 |

Equations solver categories